The Use of a Self-Instruction-Based CTL Model to Enhance Learning Focus in Hyperactive Students - Nafisatuzzahroh, Umi (Journal of Blended and Technical Education, 2026)
Objective: This study aims to describe the implementation of a Contextual Teaching and Learning (CTL) model integrated with self-instruction techniques and to analyze changes in attention, on-task behavior, and impulse control among hyperactive students in an inclusive elementary classroom. Research Design & Methods: A qualitative interactive case study design was employed. The primary subjects were students identified by teachers as exhibiting hyperactive characteristics within the ADHD spectrum, supported by classroom teachers and school staff as informants. Data were collected through classroom observations, questionnaires (teachers and students), and semi-structured interviews. Data were analyzed using interactive techniques (data reduction, display, and conclusion drawing), with source and method triangulation as well as member checking to ensure credibility. Findings: The integrated CTL–self-instruction model was implemented through structured stages (modeling, inquiry with diagnostic assessment and contextual video, questioning, learning community, constructivism, reflection, and authentic assessment). The findings indicate consistent improvement across focus-related indicators: increased duration of attention, better compliance with instructions, reduced impulsive behavior, and greater task completion independence. Questionnaires further revealed enhanced engagement, improved self-control, clearer task understanding, and higher learning interest. Contributions: The study provides practical and conceptual insights into adaptive instructional strategies that strengthen executive functioning and self-regulation in inclusive classrooms. Novelty: This research proposes a systematic integration of constructivist CTL stages with cognitive-behavioral self-instruction phases, prioritizing focus and behavioral regulation rather than solely academic achievement.